Catholic progressives in England after Vatican II - Corrin, Jay P. (University of Notre Dame Press, 2013)
Intro -- Title Page -- Copyright Page -- Dedication -- Contents -- Acknowledgments -- Introduction -- Part One. The English Cultural Setting -- One. The Church in England -- Two. The Sources of English Catholic Radicalism -- Three. English Catholics and the Establishment -- Part Two. The Reformers -- Four. Reinforcing the Citadel -- Five. The Role of John XXIII -- Six. The Council -- Seven. Vatican II Comes to Britain -- Part Three. The Revolutionaries -- Eight. The Catholic New Left -- Nine. The Slant Movement -- Ten. The Quest for New Community and Culture -- Eleven. Jesus and Marx: A Christian-Marxist Convergence? -- Twelve. Charles Davis and the McCabe Affair -- Thirteen. What Must Be Done? The Catholic Left and British Politics -- Fourteen. Legacy and Impact -- Notes -- Bibliography.